A organização do tempo e espaço na proposta curricular no Curso de Edificações do IFPA - Nascimento, Marilene Ferreira do (2012)
This dissertation is the result of a research for Masters in Education in the line of social movements, and has as its theme the organization of time and space in the draft curriculum of the course of Buildings of IFPA. It aims to analyze the relationship between time and space in the curriculum in action of the course of Buildings of the PROEJA (Programa Nacional de Integração da Educação Profissional com a Educação Básica, in the form EJA), offered by IFPA. It aims to identify the concepts and principles that addresses the new forms of organization of the curriculum PROEJA; to identify the relationships between time and space in curriculum development; and also to identify the methodologies that meet the needs of students over time and space in PROEJA. Uses a qualitative methodological approach, in which it was based on a literature on the subject, with the purpose of the theoretical basis involving the problem. Presents a reflection and analysis of official documents on the subject. Parallel to the second step, applies questionnaires to students and teachers who are part of the course in focus. At this phase, it objectives to characterize the subjects in the personal aspects and level of knowledge about the program. Approaches the development focus group, at first with students and then with teachers who conversed on the subject, encouraged to talk about their experiences involving the school. Verifies that the approachment allowed to the participants a better interaction, favoring the exchange of information. Uses as theoretical and documentary support the studies of Arroyo, Lima, Dante Henrique Moura, Maria Ciavatta, Frigotto and Freire; also the Educational Project of the course of Buildings of IFPA for PROEJA and other official documents that underlie the program. As a result of the analysis of documents and plans to travel PROEJA performed in this work, emphasizes that the concept of integration from the axis Science, Culture, Work and Technology are closer to the actions of individuals, teachers, students, managers who design integration of knowledge, as suggested by the Base Document PROEJA. Concludes that in the course plans and their policies there is no manifestation of integration across disciplines to create new knowledge or knowledge embedded in the organization beyond the disciplinary hierarchy of content. What is found in the curricular requirements are forecasts that integration should occur from a dialogue between the disciplines and the exchange of experiences among teachers. Reveals, at last, that the materialization of the concept of integration in individual stocks and methodological far the discussion needed to break the barriers between different areas and teachers from different disciplines and the possibilities of integration between the different theorists.